2014
DOI: 10.1007/s00436-014-3769-0
|View full text |Cite
|
Sign up to set email alerts
|

Serologic survey for exposure following fatal Balamuthia mandrillaris infection

Abstract: Granulomatous amebic encephalitis (GAE) from Balamuthia mandrillaris, a free-living ameba, has a case fatality rate exceeding 90% among recognized cases in the United States. In August 2010, a GAE cluster occurred following transplantation of infected organs from a previously healthy landscaper in Tucson, Arizona, USA, who died from a suspected stroke. As B. mandrillaris is thought to be transmitted through soil, a serologic survey of landscapers and a comparison group of blood donors in southern Arizona was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Free-living amoebas (FLA) are environmental protozoan parasites that can cause fatal diseases during immunosuppressive treatment. FLA are isolated from soil, sand, ponds, streams, tap water, sea water, physiotherapy pools, and other environmental sources [ 51 , 52 ]. There are three clinical presentations of amoebiasis: granulomatous amoebic encephalitis (GAE), disseminated amoebic disease and amoebic keratitis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Free-living amoebas (FLA) are environmental protozoan parasites that can cause fatal diseases during immunosuppressive treatment. FLA are isolated from soil, sand, ponds, streams, tap water, sea water, physiotherapy pools, and other environmental sources [ 51 , 52 ]. There are three clinical presentations of amoebiasis: granulomatous amoebic encephalitis (GAE), disseminated amoebic disease and amoebic keratitis.…”
Section: Resultsmentioning
confidence: 99%
“…Initial symptoms involve the skin, sinuses or lungs. Multiple recurrent panniculitis-like subcutaneous nodules with eosinophilia, chronic rhinitis and chronic sinusitis are observed [ 51 , 52 ]. The disease becomes rapidly fatal when protozoa cross the blood–brain barrier.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CSF findings of B. mandrillaris infection in the CNS resemble those of Acanthamoeba infections and include pleocytosis with lymphocytic predominance, elevated protein count and moderate hypoglycorrachia; although a normal CSF profile has also been reported. [6][7][8] Cysts and trophozoites may be visible in CSF and can confirm the diagnosis. In a microscopic examination of fresh, non-centrifuged CSF, actively moving trophozoites may be present.…”
mentioning
confidence: 97%
“…However, a serologic survey following a fatal case of B. mandrillaris infection in a previously healthy landscaper found that exposure to the organism seems to be far more common than the development of granulomatous amebic encephalitis. 6 It is therefore possible that other factors play an important role in disease pathogenesis such as amoeba virulence, frequency of exposure to contaminated soil, organism load, climatic conditions, soil biochemical characteristics or even host genetic factors.…”
mentioning
confidence: 99%